Mitigating the African Economic Crisis Through Financial Inclusion - Irem, Collins Okechukwu; Edeh, Friday Ogbu; Sherifah, Nakacwa Kasozi; Duruzor, Gloria Ifeoma; Nwoba, Charles Chukwuma; Ukaidi, Chris U.A; Oben, Desmond Neji (AIBPM Publisher, 2024)
This study examines the mitigation of the African economic crisis through financial inclusion. The paper undertakes a comprehensive exploration of the African economic landscape, navigating through historical intricacies, structural challenges, and global influences. Grounded in a quantitative methodology, the study adopted the survey method to systematically unravel the multifaceted dimensions of the economic crisis and financial inclusion in Africa. The study was anchored on both Monetarist and Keynesian models. Monetary and Keynesian financial theories were made suitable because both focus on strategies for addressing economic instability even though they take distinct approaches to solving economic issues. A sample size of 350 participants was studied, using a purposive sampling technique. The data from the returned questionnaires were selected, collated, and analyzed using tables and percentage computation. The historical overview uncovers the persistent impact of colonization and post-independence struggles, shaping the structural issues that underpin the economic challenges faced by African nations. The analysis extends to the intricate dance of global economic dynamics, examining the interplay of trade relations, the imbalance of financial services, and the complexities of the interconnected global economy. Findings indicate that financial services and products are insufficient in Africa. The study discovered that cultural, technological, and regulatory limits all significantly contribute to the economic crisis, which is evidenced by the high rate of currency devaluation in Africa, high rates of inflation in the price of goods, and economic downturns. Thus, the paper recommends that; fin-tech companies, appropriate technology applications, and advancements in online payments could potentially save this predicament. The paper further recommends that; the government should enact regulatory changes that lower entrance barriers for financial institutions, support innovation, and safeguard consumers to advance financial inclusion.